Endophytic Klebsiella aerogenes HGG15 stimulates mulberry growth in hydro-fluctuation belt and the potential mechanisms as revealed by microbiome and metabolomics - Ou, Ting; Gao, Haiying; Jiang, Kun; Yu, Jing; Zhao, Ruolin; Liu, Xiaojiao; Zhou, Zeyang; Xiang, Zhonghuai; Xie, Jie (Frontiers in Microbiology, 2022)
Growth promotion and stress tolerance induced by endophytes have been observed in various plants, but their effects on mulberry regularly suffering flood in the hydro-fluctuation belt are less understood. In the present study, endophytic Klebsiella aerogenes HGG15 was screened out from 28 plant growth promotion (PGP) bacteria as having superior PGP traits in vitro and in planta as well as biosafety for silkworms. K. aerogenes HGG15 could actively colonize into roots of mulberry and subsequently transferred to stems and leaves. The 16S ribosomal RNA (V3-V4 variable regions) amplicon sequencing revealed that exogenous application of K. aerogenes HGG15 altered the bacterial community structures of mulberry roots and stems. Moreover, the genus of Klebsiella was particularly enriched in inoculated mulberry roots and was positively correlated with mulberry development and soil potassium content. Untargeted metabolic profiles uncovered 201 differentially abundant metabolites (DEMs) between inoculated and control mulberry, with lipids and organo-heterocyclic compounds being particularly abundant DEMs. In addition, a high abundance of abiotic stress response factors and promotion growth stimulators such as glycerolipid, sphingolipid, indole, pyridine, and coumarin were observed in inoculated mulberry. Collectively, the knowledge gained from this study sheds light on potential strategies to enhance mulberry growth in hydro-fluctuation belt, and microbiome and metabolite analyses provide new insights into the growth promotion mechanisms used by plant-associated bacteria.